2019
DOI: 10.1002/aocs.12286
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Emulsifying Activities of Corn Gluten Meal Hydrolysates in Oil‐in‐Water Emulsions

Abstract: Corn gluten meal (CGM) is a protein-rich coproduct generated during corn wet milling. In this study, CGM was hydrolyzed using Neutrase protease for 1 and 3 hours, respectively, to obtain antioxidative corn gluten meal protein hydrolysates (CGMPH), which could be a potential antioxidant in various products to retard lipid oxidation. Our objective was to evaluate the emulsion properties and oxidation stability of oil-in-water emulsions containing different types (1-hour and 3-hour hydrolysates) and amounts of CG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Sivaraman et al ( 179 ) reported that the squid protein hydrolysate generated by papain has a comparable lipid peroxidation inhibitory capacity as ascorbic acid in the sardine ground meat model system. Similarly, zein hydrolysate has been shown to suppress lipid oxidation, diminish hydrogen peroxide and TBARS generation, and considerably increase the oxidative stability of model oils ( 180 ). Furthermore, this hydrolysate shows no adverse effects on emulsion quality and could be used as an effective antioxidant in food emulsion ( 181 ).…”
Section: Applications Of Bioactive Peptidesmentioning
confidence: 99%
“…Sivaraman et al ( 179 ) reported that the squid protein hydrolysate generated by papain has a comparable lipid peroxidation inhibitory capacity as ascorbic acid in the sardine ground meat model system. Similarly, zein hydrolysate has been shown to suppress lipid oxidation, diminish hydrogen peroxide and TBARS generation, and considerably increase the oxidative stability of model oils ( 180 ). Furthermore, this hydrolysate shows no adverse effects on emulsion quality and could be used as an effective antioxidant in food emulsion ( 181 ).…”
Section: Applications Of Bioactive Peptidesmentioning
confidence: 99%
“…In the sardine minced meat model system, the squid protein hydrolysate prepared by Papain has similar lipid oxidation inhibition ability as ascorbic acid [247]. Zein hydrolysate has been proven to effectively inhibit lipid oxidation, reduce the production of hydrogen peroxide and TBARS, and significantly improve the oxidative stability of model oils [248]. Moreover, this hydrolysate has no negative effect on the quality of the emulsion, and may become an effective antioxidant in food emulsion [249].…”
Section: Functional Ingredients To Stabilize Food Qualitymentioning
confidence: 99%
“…In the case of our study, the increase of the LPH concentration could have facilitated higher rate of binding of released pro‐oxidants during storage, while the surfactants were responsible for the stabilization of the emulsions. Reduction in the TBARS values with increasing concentrations of protein hydrolysates have been reported by researchers 38,40,41 . Variety of plant protein hydrolysates have been used in lipid dispersions as antioxidants, but the number of the studies that have used animal protein hydrolysates are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in the TBARS values with increasing concentrations of protein hydrolysates have been reported by researchers. 38,40,41 Variety of plant protein hydrolysates have been used in lipid dispersions as antioxidants, but the number of the studies that have used animal protein hydrolysates are limited. Consistent with our results, porcine bone hydrolysates could limit lipid oxidation in emulsions prepared with soybean oil and Tween 20.…”
Section: Discussionmentioning
confidence: 99%